Leonidov in the Crimea. Part 2 - Zavadovsky, Petr (project baikal, 2023)
In the second part of this series devoted to Leonidov’s projects for the southern coast of the Crimea, the author considers the design for Yalta and the cultural and sports facilities on the Darsan hill and the adjacent park. An attempt is made to reconstruct the main buildings on the basis of the architect’s drawings and sketches.
Keywords: I. I. Leonidov; the southern coast of the Crimea; Yalta; graphic reconstruction; late constructivism